A Financial Analysis of John Wood Group Plc - Suleiman, M. B.; Opio, S. A.; Ariko, J.; Ssali, E. (Advances in Social Sciences Research Journal, 2018)
This report focuses on the financial analysis of John Wood Group Plc. It was aimed at analysing the company’s risk profile with regards to business risk, systematic risk, financial risk, and trend and comparative analysis. Furthermore, it also aimed at evaluating four approaches to company valuation, and the past and possible future agency problems in the company. The report used the company’s annual accounts from 2010 to 2013 and for comparative purpose, two peers were considered. It was observed from the analysis that the business risk and systematic risks were high while the financial risk was low. On the company valuations, the Dividend Valuation Model (DVM) was selected among other models because the DVM computed value of the company was closest to the market value. More so, it was also observed based on the analysis that agency problems existed in the past and could possibly occur in the future. The report recommended that the company’s business risk could be minimised by maintaining high operating leverage during boom and low operating leverage during recession. In doing this, it suggested the need for trade-off between financial leverage and operating leverage. Furthermore, the reported recommended various measures the company could mitigate and avert possible occurrence of agency problem.